Acetic acid production of Lactobacillus strains isolated from chicken gut cultured in the presence of oligosaccharides - Poothan Mookiah, Saminathan; Sieo, Chin Chin; Ramasamy, Kalavathy; Abdullah, Norhani; Ho, Yin Wan (2008)
Lactobacillus species produce organic acids such as lactic and acetic acids as the end-products in the presence of organic substrates such as glucose and oligosaccharides. The effect of prebiotic fructooligossacharides (FOS) and oligomate 55N on the production of acetic acid by three probiotic Lactobacillus strains isolated from chicken gut was investigated by applying in vitro methodologies. Probiotic Lactobacillus strains (L. reuteri C 16, L. gallinarum I 16, and L. brevis I 218) were cultured separately at 37°C for 0, 3, 6, 9, 12, 15, 18 and 24h in basal MRS broth media containing either 1% prebiotic FOS, oligomate 55N or glucose (control). At the end of each incubation period acetic acid was determined using gas chromatography. The results showed that at the substrate concentration of 1% glucose or 1% oligomate 55N, production of acetic acid by Lactobacillus reuteri C 16 was the highest (maximum concentration of 16.75±1.27 and 17.63±1.19 mM, respectively) and fastest among the three Lactobacillus strains. Lactobacillus brevis I 218 produced the lowest amount of acetic acid compared to the other two Lactobacillus strains. The highest acetic acid yield from L. brevis I 218 was recorded when glucose was used as the substrate (maximum concentration of 6.78±0.43 mM) followed by oligomate 55N and FOS (maximum concentration of 4.06±0.59 and 2.81±1.43 mM, respectively). Probiotic L. gallinarum I 16 produced the highest concentration of acetic acid at 24h in the presence of FOS followed by glucose and oligomate 55N. In conclusion, the study showed that oligosaccharide substrates highly affected the production of acetic acid by the three Lactobacillus strains.